The Role of Islamic Education in The Principal's Managerial Analysis in Improving Teacher Creativity at Man 1 and Man 3 - A Habiburrahman; Nasir Usman; Niswanto Niswanto; Murniati AR (Eduprof : Islamic Education Journal, 2026)
The managerial role of the principal at MAN 1 and MAN 3 South Aceh is important in creating a supportive work atmosphere, providing motivation, and providing training to improve teacher creativity in learning. The approach used in this study is a qualitative approach with a descriptive method. Data collection techniques were carried out through observation, interviews, and documentation, with research subjects being the principal and teachers. The results 1). The managerial planning of the principal at MAN 1 and MAN 3 South Aceh designed a structured and collaborative program to improve teacher creativity, including training, professional development, and the use of technology, despite limited facilities, 2). The principal's managerial is implemented well through training and creating a positive work environment and supporting teachers in overcoming challenges, 3). program support in the form of supervision and coaching to teachers and collaborative work atmosphere transforming theological values ​​such as Shura (consultative), Amanah (integrity), and Ulul Amri (responsible authority) into practical managerial instruments. Teacher creativity emerges as a manifestation of the principles of Iqra' and Tafakkur, where teachers view pedagogical innovation as a form of worship (Ihsan). The conclusion of this study shows that the principals at MAN 1 and MAN 3 South Aceh play an important role in enhancing teacher creativity through Islamic education management that has a spiritual dimension that distinguishes it from secular management. These findings recommend the need to strengthen prophetic leadership for madrasah principals to create an innovative educational ecosystem but still based on Qur'anic values.